(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
This work analyses the impact of social network sites on the life of a university student in terms of intensity of use, personal life satisfaction, social trust, social expression and physical health. Study is based on close end survey design and consists of one hundred and fifty-four (154) respondents of four constituent campuses of Pokhara University, Nepal. The study uses both descriptive and inferential statistical methods to analyze data, draw conclusions and forward recommendations of the study. Chi-square test is also performed on the identified variables under investigation to calculate association among them. The work summarizes both the positive as well as negative aspects of using social network sites on the life university students that helps to build an understanding of role of technology in their life. Further, this study can serve as a base in identifying the socio-psychological aspects of technology of human life. For universities of under developed countries like Nepal, this can be a vital study in understanding technology and its application in academia.